Relationship Between Working Posture and Musculoskeletal Disorders Based on REBA and Nordic Body Map Analysis in Peanut Farmers - Budiyanto, Tri; Sandra, Angga Maulana; Yusuf, M (Journal of Engineering, Technology, and Applied Science (JETAS), 2025)
This research was conducted on peanut farmers in Manggung Hamlet, Tileng Village, Girisubo District, Gunungkidul Regency, Yogyakarta. Based on the results of observations, it can be seen that when harvesting peanuts, farmers were found in a bent and squatting position. In this position, farmers experience pain in the neck, back and knees when working. This study aims to determine the relationship between farmers' working posture and the level of Musculoskeletal Disorders (MSDs) complaints. The risk level of working postures is assessed using the Rapid Entire Body Assessment REBA method. The number of respondents in this study was 50 peanut farmers. The research results showed that assessment of working posture of peanut farmers using the REBA method, which obtained a score of 13, can be concluded from the total score in the high risk category where immediate action is needed to improve work posture. The frequency based on working posture shows that farmers who have a high-risk working posture are 21 respondents with a percentage (42%), and farmers who have a very high-risk working posture are 29 respondents with a percentage (58%). There is a relationship between the working posture of peanut farmers and the musculoskeletal disorders when they are working with a p-value of 0.034 (significant relationship).